(untitled) (Research, Society and Development, 2020)
Introduction: Nonviolent Communication is a method developed by Marshall Rosenberg, which seeks to provide a relationship of self-responsibility and honesty in personal relationships, through the development of empathy, deep listening and understanding of human needs and emotions. Objective: To introduce a culture of empathy, mediate conflicts, develop connection skills and meaningful conversations. Methodology: Through the so-called Person-Centered Approach (ACP), fortnightly meetings were held from June to June 2019, using strategies such as the peace-building circles other suggested by the group. Results and discussion: We observed that the results obtained were positive and that considering the feelings and needs of the leader and team member interfered significantly for the better, also reflecting on better results, which still need to be measurable in numbers. Conclusion: It was perceived an optimistic view as to the understanding that groups of empathic wheel can transmit more and more the ideal of establishing more meaningful relationships.